2009
DOI: 10.1002/smj.831
|View full text |Cite
|
Sign up to set email alerts
|

Polychronicity in top management teams: The impact on strategic decision processes and performance of new technology ventures

Abstract: Citation: Souitaris, V. & Maestro, B. M. M. (2010). Polychronicity in top management teams: The impact on strategic decision processes and performance of new technology ventures. Strategic Management Journal, 31(6), pp. 652-678. doi: 10.1002/smj.831 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent POLYCHRONICITY IN TOP MANAGEMENT TEAMS: THE IMPACT ON STRATEGIC DECISION PROCESSES AND PERFORMANCE OF NEW TECHNOLOGY VENTURES ABSTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(220 citation statements)
references
References 104 publications
(161 reference statements)
5
211
1
3
Order By: Relevance
“…This indicated that time management of an individual should consider training and controlling to understand the difference between one another. It should be noted that several organizations prefer polychronicity to increase their competitive advantage (Love, 2009;Souitaris & Maestro, 2010;Zhang, 2013). Polychronicity will be significant if it's connected to personality of extraversion, agreeableness and openness to experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that time management of an individual should consider training and controlling to understand the difference between one another. It should be noted that several organizations prefer polychronicity to increase their competitive advantage (Love, 2009;Souitaris & Maestro, 2010;Zhang, 2013). Polychronicity will be significant if it's connected to personality of extraversion, agreeableness and openness to experience.…”
Section: Discussionmentioning
confidence: 99%
“…Research findings of Souitaris and Maestro (2010) explained that polychronicity has a positive effect on company performance in a dynamic unanalyzable environments condition. This effect is partially mediated by decision speed and comprehensiveness.…”
Section: Time Orientation and Csr Strategymentioning
confidence: 95%
“…Schumpeterian perspectives of competitive advantage emphasise the importance of decision speed relative to rivals-decisions must be made quickly enough to keep pace with the rate of change in the external environment (D'Aveni, 1994;Galbraith, 1973;Thompson, 1967) in order to drive effective adaptation. Hence, the ability to make strategic decisions quickly is a key source of competitive advantage for many firms because fast decision-making enables firms to respond rapidly to rivals' competitive moves (Bourgeois & Eisenhardt, 1988;Souitaris & Maestro, 2010), to capitalize on fleeting opportunities before they disappear (D'Aveni, Dagnino, & Smith, 2010), and to gain first mover advantages by becoming early adopters of new technologies and processes (Makadok, 1998).…”
Section: Strategic Decision Speedmentioning
confidence: 99%
“…Baum & Wally, 2003;Eisenhardt, 1989;Judge & Miller, 1991;Souitaris & Maestro, 2010). Eisenhardt (1989), in her seminal study of eight high technology organizations, observed a relationship between fast strategic decision-making and subsequent sales growth and profitability in high velocity environments.…”
Section: Strategic Decision Speedmentioning
confidence: 99%
See 1 more Smart Citation